Kompetensi Pendidik Ideal Berbasis Al-Qur'an (Telaah terhadap Q.S. Luqman; 12, Q.S. Ar-Rahman: 1-5, Q.S. An-Najm: 3-10, Q.S. An-Nahl: 43-44) - Akmal Rizki Gunawan (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Al-Qur'an-Based Ideal Educator Competencies (A study of Q.S. Luqman; 12, Q.S. Ar-Rahman: 1-5, Q.S. An-Najm: 3-10, Q.S. An-Nahl: 43-44)The purpose of this study is to analyze theoretical concepts regarding the competence of ideal educators based on the Quran. In this study, the author used the maudhu'i interpretation method, which served to comprehensively explore the thematic ideas of the "ideal educator" in the Qur'an. This paper finds, in Q.S. Lukman; 12 it can be understood that the ideal educator has an argumentative scientific competence that is clean from fallacies, stupidity, so as to change the situation towards the improvement of the aqidah, worship, and morals of the learners. in addition, he also has a gentle and persuasive attitude in conveying messages. In Q.S. Ar-Rahman: 1-5 it can be understood, that the ideal educator is one who is able to teach his students to communicate both orally and in writing. In Q.S. An-Najm: 3-10, it can be understood among the traits that the teacher needs to possess are; a. Physically and mentally strong, (شديدالقوي), b. Intelligent and intellectually high (ذُو مِرَّةٍ), c. Have talents as educators that can be seen from words, behaviors, and deeds (استوى), d. Always establish closeness with students in order to understand and encourage them to move forward ( دنا ), e. Understanding the character as well as the shortcomings of each learner (تدلي), f. Always make efforts to improve in ability as a professional teacher (اْوحى), g. Meet the demands of the curriculum and syllabus (مااْوحى). in Q.S. An-Nahl: 43-44 understandably, the educator must be good at it (Ahl Zikr), in other words his knowledge is broader than the learner. The teacher must also have good handbooks (bayyinat) and diktats (zubur).